Ag85-focused T-cell immune response controls Mycobacterium avium chronic infection - Rodrigues, Bruno Miguel Cerqueira (2018)
CD4+ T cells are essential players for the control of mycobacterial infections. Several mycobacterial antigens have been identified for eliciting a relevant CD4+ T cell mediated-immune response, and numerous studies explored this issue in the context of Mycobacterium tuberculosis infection. Antigen 85 (Ag85), a highly conserved protein across Mycobacterium species, is secreted at the early phase of M. tuberculosis infection leading to the proliferation of Ag85-specific CD4+ T cells. However, in the context of Mycobacterium avium infection, little is known about the expression of this antigen and the elicited immune response. In the current work, we investigated if a T cell receptor (TCR) repertoire mostly, but not exclusively, directed at Ag85 is sufficient to mount a protective immune response against M. avium. We show that P25 mice, whose majority of T cells express a transgenic TCR specific for Ag85, control M. avium infection at the same level as wild type (WT) mice up to 20 weeks post-infection (wpi). During M. avium infection, Ag85 antigen is easily detected in the liver of 20 wpi mice by immunohistochemistry. In spite of the propensity of P25 CD4+ T cells to produce higher amounts of interferon-gamma (IFNγ) upon ex vivo stimulation, no differences in serum IFNγ levels are detected in P25 compared to WT mice, nor enhanced immunopathology is detected in P25 mice. These results indicate that a T cell response dominated by Ag85-specific T cells is appropriate to control M. avium infection with no signs of immunopathology.